Seasonal cycle of precipitation variability in South America on intraseasonal timescales - Carolina S. Vera; Mariano S. Alvarez; Paula L. M. Gonzalez; Brant Liebmann; George N. Kiladis (Climate Dynamics, 2018)

Extreme precipitation events and their relationship with ENSO and MJO phases over northern South America - Marília Harumi Shimizu; Tércio Ambrizzi; Brant Liebmann (International Journal of Climatology, 2017)
Several droughts and floods in Amazonia and Northeast Brazil have occurred in recent years and projections from Intergovernmental Panel on Climate Change indicate an increase of these extreme events. El Niño Southern Oscillation ( ENSO ) is one of the phenomena associated with extreme rainfall events in the Amazon. However, recent studies have indicated that the basic response of ENSO is dependent on the Madden–Julian Oscillation ( MJO ) phase. Hence, this study analyses the MJO influence on precipitation extreme events over northern South America in El Niño and La Niña years. Extreme precipitation events over northern South America for the rainy season (December–May) were obtained through a composite analysis of the combinations of ENSO and MJO phases. Most of the dry extreme events occurred during El Niño periods, while wet extreme events were more recurrent during La Niña or neutral years. However, the results showed that the MJO convection could enhance or weaken the basic response of ENSO on extreme precipitation events. Moreover, dry/wet extreme events over both Amazon and Northeast Brazil are favoured when MJO convection over Indonesia is enhanced ( MJO phases 4 and 5)/suppressed ( MJO phase 2). Additionally, the interannual variability of the extreme events showed an increasing linear trend for dry extreme events and a decreasing linear trend for wet extreme events. The results presented here contribute to a better understanding of the climate variability and will be helpful for the forecast of ENSO effects on extreme events over northern South America.

A comprehensive analysis of trends in extreme precipitation over southeastern coast of Brazil - Marcia T. Zilli; Leila M. V. Carvalho; Brant Liebmann; Maria A. Silva Dias (International Journal of Climatology, 2017)
Southeast Brazil ( SE Brazil) is the most densely populated region in Brazil. Previous studies have shown evidence of positive trends in average precipitation and extreme events in a few locations, suggesting the increase in rainfall‐related hazards with potential impacts to urbanized areas of SE Brazil. This study provides a comprehensive analysis of the spatial variability of trends in extreme precipitation over SE Brazil focusing on regional and local scales. We examine two daily rainfall datasets with more than 70 years of data: individual stations and gridded observed precipitation data. Our results indicate that the frequency of both rainy days and extreme daily precipitation events have increased in Sao Paulo state. Conversely, precipitation has become more concentrated in fewer events in Rio de Janeiro and Espirito Santo states where both data sets indicate positive trends in the intensity of extreme daily rainfall. The increases in frequency and intensity of extreme events have both contributed to positive trends in total seasonal and average daily precipitation over Sao Paulo. Additionally, the individual stations indicate negative trends in the number of light rainy days over large urbanized areas in the state of Sao Paulo. The spatial patterns of trends indicate that they are influenced by the proximity of large urban centres and topographic features, and also suggest variations and changes in the major climatic systems affecting precipitation regimes over SE .

Observed and simulated impacts of the summer NAO in Europe: implications for projected drying in the Mediterranean region - Ileana Bladé; Brant Liebmann; Didac Fortuny; Geert Jan van Oldenborgh (Climate Dynamics, 2012)

The South American Monsoon System and the 1970s climate transition - Leila M. V. Carvalho; Charles Jones; Ana E. Silva; Brant Liebmann; Pedro L. Silva Dias (International Journal of Climatology, 2011)
The South American Monsoon System (SAMS) is characterised by intense convective activity and precipitation during austral summer. This study investigates changes in the onset, demise and duration of SAMS during 1948–2008. The results show a significant change in these characteristics in the early 1970s. Onset becomes steadily earlier from 1948 to early 1970s and has occurred earlier than 23–27 October after 1972–1973. Demise dates have remained later than 21–25 April after the mid‐to‐late 1970s. SAMS duration shows a statistical changepoint in the summer of 1971–1972 such that the mean duration was ∼170 days (1948–1972) and 195 days (1972–1982). Vertically integrated moisture flux is used to diagnose changes in mean state and reveal statistically significant increases over South America after 1971–1972. Copyright © 2010 Royal Meteorological Society

Moisture transport and intraseasonal variability in the South America monsoon system - Leila M. V. Carvalho; Ana E. Silva; Charles Jones; Brant Liebmann; Pedro L. Silva Dias; Humberto R. Rocha (Climate Dynamics, 2011)